Labor and Economic Reforms in Latin America and the Caribbean - Edwards, Alejandra Cox 1954- (The World Bank, 1995)
Over the past decade, most countries in the Latin America and Caribbean Region have stabilized their economies and lowered barriers to international trade. Many of the policies aimed at reducing poverty and tackling inequality in the 1960-1980 period were well intentioned, but the region made little or no progress in improving income distribution. With the recent shift toward market orientation and openness to international trade, these countries will need a new approach to labor policy as well as different instruments for addressing income distribution goals. This report gives special attention to four areas of labor policy: 1) change from direct government intervention in wage determination and strict seniority rules to a system that rewards effort, high productivity, and good management within a framework that relies on voluntary negotiation of working conditions between workers and firms; 2) replacement of job security legislation by a more effective mechanism that protects workers when they change jobs; 3) careful design of mandatory contributions to social security and other programs in order to minimize the distortionary effect of labor taxes; and 4) redirecting of government subsidies for training and education to the demand side and targeting to those who cannot afford to pay